Distributed coordination of physically-interconnected multi-agent systems with actuated and unactuated agents. (November 2022) - Malan, Albertus Johannes; Pfeifer, Martin; Hohmann, Sören
Abstract: In this paper, we consider a physically-interconnected multi-agent system consisting of actuated and unactuated agents. The coordination of such a system seeks to ensure that all agents reach consensus through appropriate control of only the actuated agents. We propose a three-stage distributed control structure which achieves coordination by supplying the actuated agents with a common setpoint based on measurement information from both actuated and unactuated agents. This control structure comprises local PI controllers and dynamic distributed averaging with nearest neighbour communication. The stability of the closed loop is analysed by applying a generalized Kron reduction to construct a Lur'e problem. By applying the circle criterion, an LMI is proposed which verifies the absolute stability of the system. Finally, the closed-loop performance and robustness are illustrated via simulations.